(untitled) (The Research of Medical Science Review, 2025)
In Gilgit and similar low-resource regions of Pakistan, various social, economic and cultural factors remain a key influence on contraceptive usage. To improve reproductive health and family planning, it is important to understand adoption and use of contraceptives. This study reviewed records kept by hand at the Family Planning center in Shaheed Saif ur Rehman Government Teaching Hospital/ M&CH Complex in Gilgit from January 2020 to April 2025. According to data, the use of LARCs, especially Jadelle implants and IUCDs, soared from 67 users in 2020 to 803 in 2024. Jadelle, a new way of providing contraception, is favored by many because it is highly effective and minimally affects female anatomy. Both injectable contraceptives and condoms were still preferred, although their popularity shifted from time to time. Even though contraceptives are more available, people still have difficulties starting due to cultural and money issues. In this situation, the gynaecologist is an essential stakeholder who helps pick the best contraception based on each patient’s health. This research points out that integrating gynecological guidance and family planning support with better access is important to tackle social and financial hurdles which helps women decide on birth control wisely and support good health.